Acute Viral Hepatitis with Epidemiological Focus on Hepatitis A Virus Infection and Its Clinical Course in Adults - Nayak, Manjushree; Panda, Jayanta Kumar; Patra, Umesh Chandra (International Journal of Innovative Research in Medical Science, 2019)
In this prospective study, two hundred and fifty four patients diagnosed to be having AVH were analyzed with reference to clinical profile & viral markers and statistical analysis was done. Isolated viral infection was documented in 102 (40.1%) patients where as more than one hepatotrophic viruses caused AVH in 27(10.6%) patients. Non A-E Virus was the major case of sporadic AVH (40.1%), HBV & HEV were the etiological agent in 23.6% & 25.1% respectively. HAV was detected in 16.5% of the patients and the HCV was incriminated rarely as cause of sporadic AVH. The demographic, clinical and biochemical profile amongst isolated & mixed viral infection were found to be similar. However, HBV-AVH had significant prolonged course (p<0.001) and HAV-AVH was found to have significantly higher number of patients pursing a course of relapsing hepatitis. However HAV infection amongst adults in the present study was not found to cause severe liver disease except in few cases.